Intercropping with alfalfa or soybean alleviates the continuous cropping obstacles of yam by altering the rhizosphere community and its metabolites - Pengfei Zhang; Wanghui Guan; Lili Han; Xiaoli Hu; Ailing Xu; Ruolin Wang; Xiaomin Wang (Rhizosphere, 2026)

Metabolomic insights into flavonoid migration and bioactivity enhancement in Apocynum venetum tea during hot-water brewing - Syeda Wajeeha Gillani; Kuo Xu; Ping Li; Xueli Lu; Bo Wang; Lu Wang; Juying Wang; Guosheng Wang; Ruolin Song; Tingting Ren; Chen Meng; Yiqiang Li; et al. (Food Chemistry, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

High-entropy heterogeneous design enables ultra-fatigue-resistant gel elastomers for multimodal sensing and intelligent human-machine interaction - Ruolin Wang; Baijie Cheng; Yexi Jin; Ying Xu; Jiajia Yang; Xihua Lu (Chemical Engineering Journal, 2026)

Co-modulation of overall compressibility and conductive networks on individual sensing unit for high-performance flexible tactile sensors - Yifan Liu; Zheming Zhang; Xiao Xu; Fengming Hu; Ruolin Liu; Rongmei Wang; Ming Lei; Ziyi Dai; Bingpu Zhou (Chemical Engineering Journal, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Adsorption of chlorogenic acid in aqueous solution of Chrysanthemum morifolium (Chuju) by walnut shell-derived biochar - Ying Gao; Nan Zhang; Xinran Xu; Ruolin Zhang; Jiahang Liu; Zongyao Qian; Xuelian Wang; Yunbin Qin (Food Chemistry, 2025)

Per- and polyfluoroalkyl substances and platelet-related hematotoxicity: An integrated study of in silico, toxicological, and population evidence - Dihui Xu; Jie Xiang; Ruolin Qin; Zhijian Chen; Xiaofeng Wang; Peiwei Xu; Yitao Pan; Xinhan Zhang; Yan Wang; Ping Cheng; Yuan Chen; Dandan Xu; et al. (Journal of Hazardous Materials, 2025)

Luminescence dating of core sediments from the southern coastal Bohai Sea, China, and its implications for transgression history during the Late Quaternary - Zhiqiang Xu; Yang Han; Bingpeng Yan; Mingbo Li; Ruolin Jiang; Ruonan Tian; Bohui Liu; Zihui Zhu; Weitao Yuan; Zhongping Lai (Frontiers in Marine Science, 2025)
Several marine strata have developed along the southern coastal Bohai Sea since the Late Quaternary, preserving abundant records of sedimentary evolution. This region is ideal for studying the sedimentary history of a river–sea interaction area. However, detailed sedimentological and chronological studies remain limited, mainly focusing on the estuaries of the Mihe River. In this study, 12 optically stimulated luminescence (OSL) samples were collected from the upper 20 m of a 101 m core to establish a chronological framework using quartz OSL dating. Grain-size analysis was also conducted to determine sedimentological characteristics. Results indicate that the quartz OSL ages range from >100 ka to 6.2 ± 0.4 ka, and we believe they were the minimum ages when equivalent dose (D e ) >ca. 250 Gy (sample DZK3-G07 and below) owing to OSL signal saturation. Our findings reveal a sedimentary hiatus between >100 ka and 19.8 ka. Holocene sediments are found above a depth of 8.4 m with an onset age of approximately 10.5 ka. A lacustrine layer (8.4–9.6 m) in core DZK3 was dated to 19.8–10.5 ka, which is much older than that of the limnetic and lagoon layers in other cores in this area. Based on sedimentary facies and dating results, no transgressive sediments were observed during marine isotope stage (MIS) 3, and T2 (Xianxian transgression) in the southern coastal Bohai Sea only occurred in MIS 5e. This sedimentary sequence pattern is consistent with global sea-level changes.

Buckling characteristics analysis of bucket foundations under suction installation considering geometric and installation depth effects - Dengfeng Fu; Ruizhe Xu; Shuntao Fan; Ruolin Yuan; Yue Yan; Zefeng Zhou (Ocean Engineering, 2025)

Effect of enzymatic hydrolysis on flavor enhancement of yogurt fermented by lactic acid bacteria in egg white - Qing Gao; Ruolin Xu; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Bioscience, 2025)

Characterization of liquid egg yolks hydrolyzed by phospholipase: Structure, thermal stability and emulsification properties - Ruolin Xu; Qing Gao; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Research International, 2024)

Occurrence and migration patterns of microplastics in different tidal zones of tourist beaches: A case study in the Bohai Bay, North China - Yutao Zuo; Yawen Ge; Ruolin Wang; Wanqiang Xu; Changhong Liu; Zixiao Guo; Shuo Wang; Huiyuan Jia; Yuecong Li (Journal of Environmental Management, 2024)

Electron beam irradiation treatment driven structure-function relationships of walnut meal proteins and hydrolysates - Heyu Shen; Yubing Shi; Junqing Bai; Guangming Zou; Ruolin Wang; Huaide Xu; Jun Wang; Anwei Luo (Food Hydrocolloids, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Characterization of a new greenbug resistance gene Gb9 in a synthetic hexaploid wheat - Xiangyang Xu; Genqiao Li; Guihua Bai; Ruolin Bian; Amy Bernardo; Tezera W. Wolabu; Brett F. Carver; Yanqi Wu; Norman Elliott (Theoretical and Applied Genetics, 2024)

Iron-rich industrial waste enhanced low-carbon radiation shielding functional composites - Yan Xia; Daquan Shi; Ruolin Zhao; Kunyang Yu; Minghao Liu; Hengjun Mei; Lei Xu; Yading Zhao; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

Oxidation of emerging contaminants by S(IV) activated ferrate: Identification of reactive species - Yingying Chu; Mujian Xu; Xiaoyang Li; Junhe Lu; Zhichao Yang; Ruolin Lv; Jiahang Liu; Lu Lv; Weiming Zhang (Water Research, 2024)

Study on coastal sediment budget imbalance in cells resulted from land cover change in the savanna desertification area, west Hainan Island (China) - Shilong Luo; Ruifang Jin; Jiaxin Wang; Xinhao Wang; Manyu Huang; Mengjiao Peng; Shuolei Xu; Ruolin Zhao (Journal of Sedimentary Environments, 2024)

Quantitative trait loci for rolled leaf in a wheat EMS mutant from Jagger - Ruolin Bian; Na Liu; Yuzhou Xu; Zhenqi Su; Lingling Chai; Amy Bernardo; Paul St. Amand; Allan Fritz; Guorong Zhang; Jessica Rupp; Eduard Akhunov; Katherine W. Jordan; et al. (Theoretical and Applied Genetics, 2023)

PLAGL2 increases adriamycin resistance and EMT in breast cancer cells by activating the Wnt pathway - Yuxiao Li; Ruolin Liu; Xingzhao Han; Wei Xu; Yahui Liu (Genes & Genomics, 2023)

Identification and characterization of the novel leaf rust resistance gene Lr81 in wheat - Xiangyang Xu; James Kolmer; Genqiao Li; Chengcheng Tan; Brett F. Carver; Ruolin Bian; Amy Bernardo; Guihua Bai (Theoretical and Applied Genetics, 2022)

Decadal change in summer precipitation over the east of Northwest China and its associations with atmospheric circulations and sea surface temperatures - Shasha Shang; Gaofeng Zhu; Ruolin Li; Jie Xu; Juan Gu; Huiling Chen; Xiaowen Liu; Tuo Han (International Journal of Climatology, 2020)
As global warming has progressed, precipitation patterns over arid Northwest China have undergone significant change. In this study, changes in summer (JJA) precipitation over the eastern part of Northwest China (ENWC) from 1980 to 2014 were investigated using the China gridded monthly precipitation dataset (CN05.1). The results showed that summer precipitation over the ENWC experienced a decadal wet‐to‐dry shift in 1998. Westerlies played an important role in the upper atmospheric levels in terms of water vapour transport; the decadal variations in summer precipitation were principally controlled by the water vapour input from the ENWC's western boundary. In addition, the decadal variations in summer precipitation in the ENWC appear to be associated with a meridional teleconnection around 110°E and a zonal pattern over 45–60°N in the lower troposphere. These two teleconnections led to cyclonic anomalies in the ENWC and enhanced water vapour transport into the ENWC, resulting in above‐normal precipitation during the 1989–1998 decadal period. Further, the warmer (colder) sea surface temperatures (SSTs) observed in the tropical Eastern Pacific correspond to the southward (northward) displacement of the Asian jet stream and a negative (positive) phase of the Silk Road pattern, resulting in a wet (dry) ENWC. Moreover, the SST anomalies in the North Atlantic and Northwest Pacific may affect summer precipitation over the ENWC via a zonal teleconnection in the middle troposphere.